The melancholy according to Aristotle in the magic square on Duerer's Melencolia I - Tine Kurent (Acta Neophilologica, 1993)
In the numbers of Duerer's Melancolia  magic square is hidden the Aristotle's wonder: "How come, that all the people, excelling in philosophy or in politics or in poetry or in arts, are evidently melancholical..."